Pilot Exploration of Global Advanced Digital Agricultural Technologies in China’s Grain Production - LI Xun; PAN Chao (Liang you shipin ke-ji)
In response to the two major strategic needs of increasing national grain yield per unit area and 3rd-party professional services, this paper systematically expounds on the challenges such as climate change faced by global food production and the development opportunities in the digital age, and analyzes advanced digital agricultural technology systems in the world. Taking the construction of the BeiDou + Smart Agriculture Demonstration Base of Corn in Neihuang County, Henan Province by the United Board of Digital Agriculture of China Agricultural Machinery Distribution Association(UBDA of CAMDA) as an example, which has achieved an increase in yield per unit area and empowered 3rd-part professional services, this paper introduces the systematic application and effects of technology systems of digital agriculture, including yield maps, soil maps, precision (variable-rate) seeding, precision (variable-rate) fertilization, precision (variable-rate) spraying, BeiDou navigation, and UAV remote sensing. It also presents the demonstration and training activities carried out by the UBDA of CAMDA to promote above-mentioned technology systems. The practice in Neihuang shows that the systematic application of digital agriculture technologies has not only achieved a large-scale increase in corn yield per unit area by 24.5%, but also significantly improved the grain quality, such as reducing phyto-toxins. Moreover, it has enhanced the resilience to extreme weather and pests. The promotion of advanced digital agricultural technologies will also be conducive to ensuring national food security and the development of new quality productive forces, help establish a long-term mechanism for the comprehensive revitalization of rural areas and contribute to the achievement of the strategic goal of building an agricultural power by 2035.